Is immunotherapy here to stay in multiple myeloma? - Rodríguez-Otero, Paula (Haematologica, 2017)
Immune escape and impaired immune surveillance have been identified as emerging hallmarks of cancer.(1) Multiple myeloma represents a genuine example of disrupted immune surveillance characterized by: impaired antibody production, deregulation of the T and natural killer cell compartment, disruption of antigen presentation machinery, upregulation of inhibitory surface ligands, and recruitment of immunosuppressive cells. Although the potential value of immunotherapeutic interventions had a clear antecedent in the graft-versus-myeloma effect induced by allogeneic stem cell transplant and donor lymphocyte infusions, it is only recently that this field has faced a real revolution. In this review we discuss the current results obtained with immune approaches in patients with multiple myeloma that have placed this disease under the scope of immuno-oncology, bringing new therapeutic opportunities for the treatment of multiple myeloma patients.